2020
DOI: 10.1128/iai.00616-19
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Stage Antigen RBP2-P1 of Plasmodium vivax Binds Reticulocytes and Is a Target of Naturally Acquired Immunity

Abstract: The interactions between Plasmodium parasites and human erythrocytes are prime targets of blood stage malaria vaccine development. The reticulocyte binding protein 2-P1 (RBP2-P1) of Plasmodium vivax, a member of the reticulocyte binding protein family, has recently been shown to be highly antigenic in several settings endemic for malaria. Yet, its functional characteristics and the relevance of its antibody response in human malaria have not been examined. In this study, the potential function of RBP2-P1 as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…From a vaccine development standpoint, such research—and the use of the related P. cynomolgi and P. knowlesi parasites for fundamental basic biological studies and to generate crossreactive antibody reagents and perform basic experiments—has been critical for the identification of immunogenic merozoite surface and apically located proteins, which have been regarded as vaccine candidates (reviewed in [ 19 , 25 , 161 , 299 , 301 , 311 ]). These include the PvDBP and the Reticulocyte Binding Protein (PvRBP) family members that have been shown to adhere to reticulocytes [ 300 , 316 320 ]. Specifically, young CD71+ and CD98+ reticulocytes were identified as the host cells for P. vivax [ 13 , 318 , 321 , 322 ] (reviewed in [ 323 ]).…”
Section: Twenty-first Century—turning Point In Malaria Researchmentioning
confidence: 99%
“…From a vaccine development standpoint, such research—and the use of the related P. cynomolgi and P. knowlesi parasites for fundamental basic biological studies and to generate crossreactive antibody reagents and perform basic experiments—has been critical for the identification of immunogenic merozoite surface and apically located proteins, which have been regarded as vaccine candidates (reviewed in [ 19 , 25 , 161 , 299 , 301 , 311 ]). These include the PvDBP and the Reticulocyte Binding Protein (PvRBP) family members that have been shown to adhere to reticulocytes [ 300 , 316 320 ]. Specifically, young CD71+ and CD98+ reticulocytes were identified as the host cells for P. vivax [ 13 , 318 , 321 , 322 ] (reviewed in [ 323 ]).…”
Section: Twenty-first Century—turning Point In Malaria Researchmentioning
confidence: 99%
“…Overwhelmingly, these studies have found seroprevalence and/or higher levels of antibodies and increased prevalence of subclinical infection, despite a variety of different parasite targets investigated. 61 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 Although, like investigations of the role of acquired antimalarial Abs and protection from clinical manifestations of Plasmodium spp. infections, many studies have focused on sporozoite and merozoite‐specific responses with a lack of investigations into the role of Abs in response to the infected erythrocyte (Table 1 ).…”
Section: Humoral Immunity and The Prevalence Of Sub‐clinical ...mentioning
confidence: 99%
“…In many cross‐sectional surveys, antimalarial Abs are found at greater levels or in a greater proportion of subclinically infected individuals compared to uninfected community members for both P. falciparum and P. vivax infection across a range of transmission intensities (summarized in Table 1). Overwhelmingly, these studies have found seroprevalence and/or higher levels of antibodies and increased prevalence of subclinical infection, despite a variety of different parasite targets investigated 61,72–79 . Although, like investigations of the role of acquired antimalarial Abs and protection from clinical manifestations of Plasmodium spp.…”
Section: Humoral Immunity and The Prevalence Of Sub‐clinical Plasmodi...mentioning
confidence: 99%
“…P. vivax malaria patients had higher IgG levels against rRBP2P1 than did naive individuals. Human antibodies to this protein also exhibit erythrocyte binding inhibition and are associated with lower parasitemia [ 155 ]. PvRBP1a and PvRBP1b are highly transcribed during the parasite schizont stage [ 118 ].…”
Section: Humoral Immune Response Against P Vivax mentioning
confidence: 99%